Moderate climate sensitivity due to opposing mixed-phase cloud feedbacks - Ivy Tan; Chen Zhou; Aubert Lamy; Catherine L. Stauffer (npj Climate and Atmospheric Science)
Abstract Earth’s climate sensitivity quantifies the ultimate change in global mean surface air temperature in response to a doubling of atmospheric CO2 concentrations. Recent assessments estimate that Earth’s climate sensitivity very likely lies between 2.3 °C and 4.7 °C, with the representation of clouds in climate models accounting for a large portion of its uncertainty. Here, we adjust the climate sensitivity of individual contemporary climate models after using satellite observations to alleviate biases in their representation of mixed-phase clouds. A resulting moderate average climate sensitivity of 3.63 ± 0.98(1σ) °C arises due to opposing responses of clouds. While increasing the proportion of liquid within cold clouds prior to CO2 doubling increases climate sensitivity via transitions from solid to liquid hydrometeors, a strongly opposing increase in reflective cloud cover decreases climate sensitivity. This emphasizes the need to reconsider the role of mixed-phase cloud cover changes in climate sensitivity assessments.